LEGALITAS STATUS HUKUM TANAMAN KRATOM DI INDONESIA - Avridha Riyanti Maharani, (2021)
The existence of a plant that is cultivated or developed by humans, both in the media and in space for the results to be utilized. One of the plants that is believed to be hereditary is herbal plants, because they have properties that can heal or prevent attacks from various diseases. One of the trusted herbal plants is the kratom plant, which is effective in curing coughs, diarrhea, diabetes, pain relievers, and anti-inflammatory. In Kratom there are the alkaloids mitragynine and 7-hydroxymitragynine, kratom are often found in Southeast Asia. The growth of kratom in Indonesia is still used by the public. However, the public must be more familiar with the effects, benefits and even legality in the eyes of the law. However, kratom plants have been included in New Psychoactive Products (NPS). Currently, Indonesia still allows the circulation of kratom. Therefore, the government was asked to make the best possible policy regarding the existence of kratom which is thought to have effects such as narcotics to cause addiction.